ABCA3 lung disease in an ex 27 week preterm infant responsive to systemic glucocorticosteroids. Issue 1 (29th July 2015) - Tan, Jason KG; Murray, Conor; Schultz, Andre
Summary: We present a case of an infant born at almost 28 weeks gestation, found to be homozygous for a missense mutation of ABCA3, with diffuse lung disease that has continued throughout infancy. The patient's clinical course and chest imaging was highly suggestive of diffuse lung disease of infancy, and not of chronic lung disease of prematurity. The lung disease proved to be highly responsive to systemic corticosteroids. This is a case of ABCA3 lung disease that demonstrated improvement after systemic glucocorticosteroid administration.Pediatr Pulmonol. 2016;51:E1–E3. © 2015 Wiley Periodicals, Inc.